2022
DOI: 10.3390/ijerph19084599
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Increases the Impact of Low Back Pain: A Systematic Review and Metanalysis

Abstract: In March 2019, the World Health Organization (WHO) recognized the COVID-19 pandemic as a global issue. To reduce the spread of this disease, health safety pathways were implemented worldwide. These extraordinary measures changed people’s lifestyles, e.g., by being forced to isolate, and in many cases, to work remotely from home. Low back pain (LBP), the most common cause of disability worldwide, is often a symptom of COVID-19. Moreover, it is often associated with different lifestyle features (type of job, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 63 publications
(68 reference statements)
2
29
0
1
Order By: Relevance
“…Based on this study, the number of new diagnoses of neck and low back pain decreased in general and orthopedic practices in Germany in 2020 and 2021 compared with 2019. This decrease is of particular concern, because other bodies of research have found high rates of self-reported musculoskeletal pain in the general population since the beginning of the pandemic ( Papalia et al, 2022 , Šagát et al, 2020 ). Furthermore, post-COVID-19 syndrome following SARS-CoV-2 infection can also include musculoskeletal pain ( Aiyegbusi, O.L., Hughes, S.E., Turner, G., Rivera, S.C., McMullan, C., Chandan, J.S., Haroon, S., Price, G., Davies, E.H., Nirantharakumar, K., Sapey, E., Calvert, M.J., TLC Study Group, 2021 , Karaarslan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this study, the number of new diagnoses of neck and low back pain decreased in general and orthopedic practices in Germany in 2020 and 2021 compared with 2019. This decrease is of particular concern, because other bodies of research have found high rates of self-reported musculoskeletal pain in the general population since the beginning of the pandemic ( Papalia et al, 2022 , Šagát et al, 2020 ). Furthermore, post-COVID-19 syndrome following SARS-CoV-2 infection can also include musculoskeletal pain ( Aiyegbusi, O.L., Hughes, S.E., Turner, G., Rivera, S.C., McMullan, C., Chandan, J.S., Haroon, S., Price, G., Davies, E.H., Nirantharakumar, K., Sapey, E., Calvert, M.J., TLC Study Group, 2021 , Karaarslan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study, using data obtained at two tertiary care centers in the United States, found a decreasing trend in the number of new cases of multiple musculoskeletal conditions (e.g., knee osteoarthritis, shoulder sprain, and carpal tunnel syndrome) ( Yu et al, 2021 ). Less is known about how the COVID-19 crisis has affected the diagnosis of neck and low back pain, although some literature indicates that the pandemic has led to an increase in the prevalence of self-reported low back pain ( Papalia et al, 2022 ) and an aggravation of symptoms in people already affected by low back pain ( Bailly et al, 2022 ). To the best of the authors’ knowledge, the three only studies on this topic have been conducted in hospital settings ( Borsa et al, 2020 , Jäntti et al, 2022 , Sharma et al, 2021 ), and no data is available from primary care and specialized practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em uma recente revisão sistemática com metanálise 28 pandemia e pandêmico (p = 0,0004 e p = 0,04, respectivamente).…”
Section: Discussionunclassified
“…Previous studies have shown a higher risk of painful symptoms in the cervical regions and largely in the lumbar region 1,3,6,10,11 . However, the specificity of acute pain has not been investigated, which may not show the emergence of pain in the pandemic period in specific locations 1,3,6,10,11 . In addition, compliance with the presence of pain in overweight/obese individuals has been presented in situations of chronic pain 10,11 .…”
Section: Introductionmentioning
confidence: 98%